A Novel Scaffold-Based Hybrid Multicellular Model for Pancreatic Ductal Adenocarcinoma—Toward a Better Mimicry of the in vivo Tumor Microenvironment - Gupta, Priyanka; Pérez-Mancera, Pedro A.; Kocher, Hemant; Nisbet, Andrew; Schettino, Giuseppe; Velliou, Eirini G. (Frontiers in Bioengineering and Biotechnology, 2020)
With a very low survival rate, pancreatic ductal adenocarcinoma (PDAC) is a deadly disease. This has been primarily attributed to – (i) its late diagnosis and (ii) its high resistance to current treatment methods. The later, specifically requires the development of robust, realistic in vitro models of PDAC, capable of accurately mimicking the in vivo tumour niche. Advancements in the field of Tissue Engineering (TE) have helped the development of such models for PDAC. Herein, we report for the first time a novel hybrid, poly- urethane (PU) scaffold based, long term, multicellular (tri-culture) model of pancreatic cancer involving cancer cells, endothelial cells and stellate cells. Recognising the importance of ECM proteins for optimal growth of different cell types, the model consists of two different zones/compartments: an inner tumour compartment consisting of cancer cells (fibronectin coated) and a surrounding stromal compartment consisting of stellate and endothelial cells (collagen I coated). Our developed novel hybrid, tri-culture model supports the proliferation of all different cell types for 35 days (5 weeks), which is the longest reported time frame in vitro. Furthermore, the hybrid model showed extensive collagen I production by the cells, mimicking desmoplasia, one of PDAC’s hallmark features. Fibril alignment of the stellate cells was observed, which attested for their activated state. All three cell types expressed various cell specific markers within the scaffolds, throughout the culture period and showed cellular migration between the two zones of the hybrid scaffold. Our novel model has great potential as a low cost tool for in vitro studies of PDAC as well as for treatment screening.